THE DEVELOPMENT OF DOCUMENT MANAGEMENT WORKFLOW SYSTEM TO SUPPORT INTERLIBRARY LOAN SERVICE - Muhammad Taufik, Nur Hidayah (Universiti Teknologi Petronas, 2011)
This report describes system that automated interlibrary loan where it's coordinate the application process from fill in the requirement information from user side to review, approval and notification. The author defines workflow management system, interlibrary loan (ILL) and mechanism how ILL, the document driven move from user to librarian. This report describes the hardware and software used, architecture implemented and function available.